#TITLE_ALTERNATIVE# - OCTAVINALDI NURPRATAMA (NIM : 10208064); Pembimbing : Gunawan Handayani, MSCE, Ph.D, TAUPIK
Surface waves is one type of seismic waves that propagates at medium of earthÃ‚Â’s surface. Surface waves can be divided into two types based on the motion of the particles, the Rayleigh waves and the love waves. Rayleigh waves has a dispersion (spread) properties that can be used for geotechnical purposes of imaging the subsurface structure of the earth. One method that utilizes the unique characteristics of Rayleigh waves is microtremor array method. Microtremor is a natural resonance produced by the natural activities (such as earthquakes, wind, ocean waves) or human activities (such as traffic, industrial activities). This method is more efficient than conservative seismic methods (downhole, well-logging, and others) that utilize body waves because this method does not require holes in the process. Moreover, this method does not need to stop human activities so that the method is suitable to be applied in urban environments. There are two methods in microtremor measurements, thw spatial auto-correlation (SPAC) method and the frequency-wavenumber (FK) method. Both of these methods require sensors (geophones) in measurement, at least seven for FK method and four for SPAC method, and set up a an array. Array commonly used is a circular array or an equilateral triangle array. Depth can be investigated depending on the size of the observation radius. In this thesis, there is a difference in the penetration depth can be measured between FK method and The SPAC method. Furthermore, from data processing using software geopsy and dinver be obtained dispersion curves and S-wave velocity profiles. S-wave velocity profiles obtained from the inversion of the dispersion curves using software dinver. After obataining the S-wave velocity profiles, the structure of the subsurface can be immediately determined